A Comment on "How the Party Commands the Gun: The Foreign-Domestic Threat Dilemma in China" - Michael Jetter; Adhipradana P. Swasito (Institute for Replication (I4R), 2024)
Mattingly (2024) investigates how authoritarian leaders select military generals, focusing on the People's Liberation Army of China. Three main findings emerge. First, in general, Chinese leaders consider both personal ties (as a proxy for loyalty to the leader) and combat experience (as a proxy for competence) when promoting military officers. Second, personal ties are particularly relevant during periods of domestic threat. Third, combat experience only matters during periods of foreign threat. We successfully replicate all main results with Mattingly's (2024) database, only identifying minimal differences in calculated standard errors when employing Stata instead of R. However, results differ substantially in sign, magnitude, and statistical precision once we employ alternative, data-driven approaches to defining periods of domestic threat. Alternative specification results pertaining to foreign threat periods are more robust in sign but also vary in terms of magnitude and levels of statistical relevance.
Keywords: C81; C87; D74; F52; H56; N45; 330; Guardianship Dilemma; ChineseMilitary; Promotion as General; Foreign and Domestic Threats; Career Ties; Combat Experience